Humeral Capitellum Fracture Bryan-Morrey Type IV Performed Open Reduction Internal Fixation Treatment: A Rare Case Report - Fajar Ivan Effendi; Christopher Daniel Tristan; Awalil Rifqi Kurnia Rahman; Muhammad Farid Hamka; Aininna ‘Izzah Zafira; Hikam Yanwar Pradana (Plexus Medical Journal, 2026)
Introduction: Capitellum fracture is a very rare fracture with an incidence of 1% of fracture cases in the elbow area and 6% of all fracture cases in the distal humerus area. Case Report: A 41-year-old man presented to the emergency room with left elbow pain after a fall and unable to move his arm. An X-ray revealed a lateral condyle fracture (Milch type 2) with joint dislocation and soft tissue swelling. However, a CT scan showed a different fracture extending from the capitellum to the trochlear (Bryan Morrey type IV or McKee fracture). She underwent successful ORIF with K-wires, experiencing sharp pain post- procedure but recovering well overall. Discussion: The rarity of capitellum fractures is due to its protected position behind the radial head, humeral trochlea, and humeral collateral ligaments. Specific radiographic signs, like the double arc sign on lateral X-rays, are crucial for diagnosis. This sign should not be overlooked and should be confirmed by a pre-operative 3D CT scan to prevent misdiagnosis. Treatment typically involves ORIF, ideally with a Herbert screw, although K-wires can be used as an alternative in certain circumstances. Conclusion: Capitellum fracture is a very rare injury. Before surgery, a CT scan and 3D reconstruction should be conducted to evaluate the anatomy and accurately classify the fracture. The Herbert screw is considered the optimal treatment, but in emergencies or when cost is a concern, K-wires can be a suitable alternative.